A new synthetic material for the brow suspension procedure. - Cole, M D (1989)
This report describes the use of a new synthetic material, combining polyester with carbon, in nine brow suspension procedures. The mechanical properties of polyester, with the fibrous tissue inducing properties of carbon, combine to produce a scaffolding on which fibrovascular ingrowth is possible. Subsequent fibrosis gives a permanent effect. Early results indicate that the material is tolerated well in the eyelid, but the problem of early slippage remains.